Investigation on health condition of a freshwater eel, Monopterus cuchia from Ailee beel, Mymensingh, Bangladesh - Ahmed, GU; Akter, N; Nipa, SA; Hossain, MM (Journal of the Bangladesh Agricultural University, 2010)
The health conditions of freshwater mud eel, Monopterus cuchia of Ailee beel, Mymensingh district was investigated through clinical and histopathological observations from September 2005 to March 2006. Monthly sampling of water quality parameters like temperature, dissolved oxygen, pH and total hardness were carried out. Water temperature and total hardness were at reduced level for fish during the months of November to January in the beel. Clinically weak body, rough skin, deep ulcer and grey brownish colour of the body were noticed especially from November to January. Major pathology in the skin and muscle such as loss of epidermis and dermis, necrosis of myotoms, huge vacuum spaces, marked melanomacrophage and fungal granuloma were found in December and January. Marked melanomacrophages, severe haemorrhage, vaccums, hepatic necrosis, fat droplets were found in the liver. In kidney numerous haemorrhagic areas, necrosis, few fat droplets and many fungal granulomas were seen in December and January. Histopathologically, sampled fishes were found normal in September and October and reduced pathological signs were observed in February and March. Clinically and pathologically eels were found to be more affected in December and January. Reduced temperature and total hardness might have played role in the occurrence of clinical and pathological changes in fish during the period. The fishes were affected by EUS, with the evidence of development of fungal granuloma in skin, muscle and kidney. Keywords: Health; Freshwater eel; Disease; Ailee beel DOI: 10.3329/jbau.v7i2.4755 J. Bangladesh Agril. Univ. 7(2): 421-426, 2009